Pemberdayaan Keluarga Muda tentang Pencegahan Stunting Menggunakan Video Dokumenter: Empowering Young Families on Stunting Prevention Using Video Documentaries - Amalia, Maya; Fitri, Rahmania Almira; Nuraeni, Rika; Ikbari, Gissan Rafli (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
One important factor in stunting prevention is family knowledge. The family is an important subject to increase knowledge related to stunting prevention because one of the family development tasks of new couples is planning to have children. The purpose of this activity is to provide education to young families about stunting prevention with documentary video media. This activity begins with giving a pretest, then watching a documentary video, explanation, and ends with a posttest. The activity was carried out in the work area of the Cihampelas Health Centre, West Bandung. The documentary video tells a fictional family story that contains the meaning of stunting prevention starting from gestational age to feeding practices with a video duration of 9 minutes. The video was played 2 times. Respondents in this community service were 21 respondents. The results of this activity are that the majority are women, aged 25-30 years. Data analysis showed that there was a slight decrease in low and moderate knowledge, and there was a slight increase in high knowledge. There was a mean increase of 0.34 points from pretest to posttest, indicating an increase in knowledge or a change in score after the intervention or activities carried out. This community service is the provision of documentary videos can be an alternative to providing education in stunting prevention in young families, but education can be provided more frequently and repeatedly. More structured delivery of material and repetition can strengthen understanding and implementation of stunting prevention in young families.